(untitled) (Journal of Science and Technology, 2016)
A survey was conducted in the Upper East region of Ghana to seek information on the fertility status of the soils, manure production, its management options and nutrient concentration that could be associated with quality. Analysis of soils from farmers’ fields showed that the soils are coarse textured, with low exchange capacity and organic matter contents. Available P in particu- lar was very low with most of the soils having values less than 6.00 ppm. Four main types of cat- tle rearing systems were encountered; the field, kraal, compound and intensive. Fresh manure samples from each of these systems were collected air dried and analysed in the laboratory using standard protocols. The N and P contents of the manure ranged from 0.52 % to 1.14 %, and 0.28 % to 0.76 % respectively, which were below the critical levels for net mineralization. Polyphenol contents on the other hand were lower than the critical value of 4 %. Decomposition and nutri- ent release of the manure showed immobilization of total N during the first four weeks, suggest- ing the need to improve the quality by composting or applying it in combination with mineral fertilizers.